DESIGN, SIMULATION AND REALIZATION OF A COMPACT DUAL BAND MEANDERED COUPLER - R., El Bouslemti1; . F., Salah-Belkhodja2 (university of eloued جامعة الوادي, 2019)
Telecommunication systems increasingly require the use of miniaturized passive microwave components. One of these is the directional coupler, a four-port component intended to distribute power to two output ports, the fourth port being isolated. This paper proposes a dual-band branch-line coupler (BLC) with an extremely compact microstrip structure. The application of meandering lines as the coupler’s central connector yields dual-band operation. HFSS is used to optimize the device and to verify its transmission characteristics. This yields a design of a coupler with a footprint is 23×34.6 mm², operating at 1.65 / 3.30 GHz, with ports that can be adapted to a load impedance of 50 Ohm. To validate the model, the coupler is fabricated using microstrip technology on a FR4 substrate. A good agreement between measurement and simulation results is obtained. The coupler achieves an excellent isolation of –42.41 dB and a transmission loss of only –2.29 dB at 3.30 GHz.
artical
Keywords: meandered line; miniature size; dual-band; directional coupler; microstrip